Perancangan Branding Dalam Peningkatan Produk UMKM di Desa Cikangkung - Agus Darmawan; Galang Jati Zhahara; Rinaldi Ferdian; Mohammad Goldi Yogaswara; Raden Kiki Gumilar Pamungkas Haryono; Agnia Hayati Rahman; Aji Candra Revaldi; Teguh Dewa Rijki; Shafira Mega Utami; Mustika Dwi Solichin; Dikna Muharani Safitri (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2023)
Abstract Branding is an important part of introducing a product or service as a business undertaken to the public or target market. Branding is a necessity for business actors who require special attention to their products or services to increase added value to their business. A strong identity with the right design is able to reach the sales target market well. The branding design for UMKM products in Cikangkung Village is a new thing that has never been done. The branding and marketing relationship that is designed by experts will be able to describe the company's value in the product or service in the visual design that is made. The method used in this research is a qualitative descriptive method. The object of this research is the product of UMKM in Cikangkung Village. The focus of this research is on branding. The importance of research in this research in the future is to be able to provide positive value to business actors in Cikangkung Village and open a new understanding of the importance of branding on a product or service in increasing product introduction to the market and also its impact on increasing sales. The implementation of this research was carried out with the following steps: (1) Data collection of UMKM in the village area; (2) Collecting data on the natural resource potential of the village area; (3) Home-level survey of UMKM Branding in village areas; (4) Counseling on the overall level of branding and digitizing UMKM in village areas; (5) Data collection on Logo Making and promotional media for UMKM. Keyword: Branding, Design, UMKM